Perhitungan RAB dan Waktu Pekerjaan Struktur Bangunan Gedung B Sekolah Rajawali Bangsa Negeri Lama Kota Ambon : RAB Calculation and Work Time Building Structure of Building B Rajawali Bangsa School the Old Country of Ambon City - Muchlis Salamun; Pieter Lourens Frans; Maslan Abdin (Litera Academica Publishing, 2024)
Calculation of the cost and time budget for construction work aims to find out how much the budget costs and how long it will take to carry out construction work on the construction of Building B of the Rajawali Bangsa Negeri Lama School, Ambon City. Based on data obtained from the authorities working on the Rajawali Bangsa School Building B Construction Project, only working drawing data was obtained. This research aims to calculate the cost of structural work and plan the time for carrying out structural work on the construction of Building B of the Rajawali Bangsa Negeri Lama School, Ambon City. This research uses a field survey method. The results of the research show that based on unit prices for the Ambon City area in 2023, work time planning uses the S Curve method, so as to know the planned time for the duration of each work item being carried out. Based on the results of the calculations, the budget plan for the cost required for the Rajawali Bangsa School Building B Structure work is Rp. 3,450,354,000.00 and the planned duration of the Rajawali Bangsa School Building B Structure work duration is 16 weeks with 112 calendar days. So it can be suggested to calculate the budget plan for the costs and time of work that has not been achieved in the form of a budget for non-structural work costs and non-structural work time.